PEMANFAATAN LIMBAH ORGANIK PASAR SEBAGAI BAHAN BAKU PELET DENGAN PRETREATMENT SECARA FERMENTASI ANAEROB - Armen Armen; Sri Elfina; Haswan Haswan (Politeknik ATI Padang, 2022)
Processing market waste into feed can increase the added value of waste. Market waste consisting of vegetables and animals still contains nutrients that are beneficial for livestock and fish as an alternative or main feed. Utilization of market waste into fish pellets needs to be studied with a fermentation process with variations in fermentation time of 2-6 days, molasses content (5%, 10% and 15%) and animal and vegetable composition (1:1, 2:3 and 3:1) on crude protein and feed quality. The process of making feed by mixing market waste materials and a fermentation and flouring process will be carried out to obtain uniform pellets in printing. Protein test will be carried out using the Kjedhal method as crude protein content. Based on the results of buoyancy for more than 6 minutes, pellets with a composition of 50% fish offal had the best quality compared to other variations with a protein content of 32.48%.